Análise de duas práticas pedagógicas no ensino superior tecnológico : interdisciplinaridade ou problematização? - Santos, Maria Célia Calmon (2008)
This work has as context the study of two interdisciplinary teaching practices adopted by the Higher Education Institution in technology researched. We tried to know the experience of Institution and reflect on the meaning of such practices in the training of technologist, thus how to make effective these practices adopted from the integration of disciplines and content in the curriculum studied by students semesters. Part of the necessity the deepen of knowledge about the teaching practices that use these strategies to work with interdisciplinary projects in higher education technology, as well as the problem of disciplinary content focused on the reality of the world of work, which bring the student's professional context. The study identifies with a methodology called the methodology of the problem, thus bringing it closer to a proposed curriculum well adjusted to the formation of the technician because part of the experience in a context of that question will have to build their studies and looking for a more flexible as well as build solid theoretical and practical knowledge during training. The research was developed in a qualitative boarding and tried to search studying aspects of the student's learning, the curricular integration, showing how the influence of new technologies reflects the curriculum of an Higher Education Institution, so that it fits with the context the postmodern era. The instrument of collect and data was used to analyse was the questionnaire and halfstructuralized interviews with students participating in the research, coordinators of the university and responsible in the company. We realized that the practice helped in the formation of technician from the Higher Education Institution and we identify advantages, disadvantages and limitations in its operation. We finish presenting the analysis of the results, signing how the practices ift hey show as complementary in the construction of a curricular identity for a solid formation of the technician in the institution.